Qualimetry Essentials Applied to Embedded Software Development. Issue 4 (12th January 2022) - Argotti, Yann; Baron, Claude; Esteban, Phillipe
ABSTRACT: With the initial goal of filling gaps in the definition, assessment, control, and prediction of automotive embedded software quality, including standards and regulatory compliance constraints, a three‐year research study was conducted. The multiple contributions of the study to theoretical and applied qualimetry have helped to define a theoretical framework for quality control and monitoring of engineering and product development processes. Then, demonstrating the practicality of this solution, this study was applied on a real example from the automotive industry. This framework initially developed in the scope of embedded software is also applicable to systems and embedded systems, and makes these contributions have an impact on all industrial sectors.